Ancaman Eksistensial Bagi Kemanusiaan dan Kegagapan Manusia Yang Naif: : Pemeriksaan Kritis Mengenai Kecerdasan Buatan dalam Pendidikan - Agustinus Tamtama Putra (Gerakan Indonesia Kita, 2025)
There are two trends in education in the face of rapid and massive technological development, in this case Artificial Intelligence. One pole reviles Artificial Intelligence as an existential threat to humanity, while the other pole glorifies Artificial Intelligence as a genius invention, a sophisticated and reliable product of modern thinking. This paper aims to examine the strengths and weaknesses of these two polar opposites in the contemporary debate on Artificial Intelligence, particularly in the realm of education. Through a literature study in which the latest scientific research is scrutinised and tested, the author aims to clash the two schools of thought within the framework of human philosophy as a dialectical subject, along with the ethical dimensions that surround the debate on Artificial Intelligence. As a finding of the research, as well as to synthesise the two opposing poles, the author sees that the collaboration between humans and Artificial Intelligence is a necessity in this day and age because moral and ethical boundaries can only be provided when humans are truly involved and take part in the dynamics of Artificial Intelligence. Human insecurity in the face of Artificial Intelligence should also not happen because the capacity of human soul, spirit and work can never be replaced by Artificial Intelligence. The realm of education can utilise Artificial Intelligence to further advance humanity.